Intravenous Thrombolysis is Effective in Young Adults: Results from the Baden-Wuerttemberg Stroke Registry - Reuter, Björn; Gumbinger, Christoph; Sauer, Tamara; Wiethölter, Horst; Bruder, Ingo; Diehm, Curt; Ringleb, Peter A.; Kern, Rolf; Hacke, Werner; Hennerici, Michael G.; , Stroke Working Group of Baden-Wuerttemberg (Frontiers in Neurology, 2015)
Background: The efficacy of intravenous thrombolysis (IVT) is sufficiently proven in ischemic stroke patients of middle and older age by means of randomized controlled trials and large observational studies. However, data in young stroke patients ≤ 50 years are still scarce. In this study we aimed to evaluate the effectiveness and safety of IVT in young adults aged 18-50 years. We analyzed data from a consecutive and prospective stroke registry which covers a federal state with 10.8 million inhabitants in southwest Germany. Methods: Our analysis comprises of 51,735 ischemic stroke patients aged 18-80 years (y) and hospitalized from January 2008 to December 2012. Of these, 4,140 (8%) were aged 18-50y and 7,529 (15%) underwent IVT. Data on 8,439 patients (16% of the study population) were missing for National Institutes of Health stroke severity score at admission and/or mRS at discharge and were excluded from outcome analysis. In sensitivity analysis patients with incomplete data were also examined. We used binary logistic regression models adjusted for patient, hospital, and procedural parameters and stratified by age-group (18-50y and 51-80y, subgroup analyses 18-30y, 31-40y, 41-50y) to assess the relationship between IVT and modified Rankin Scale (mRS) at discharge. Results: IVT appears equally effective in young adults 18-50y (adjusted odds ratio 1.40, 95% confidence interval 1.12 to 1.75; p=0.003), compared to patients 51-80y of age (1.33, 1.23 to 1.43; p<0.001). Age stratified analyses suggest an inverse relation of age and effectiveness, which appears to be highest in very young patients 18-30y of age (2.78, 1.10 to 7.05; p=0.03). Discussion: Ischemic stroke etiology, vascular dynamics and recovery differ in young patients from those of middle and older age. The evidence from routine hospital care in Germany indicates that IVT in young stroke patients appears to be at least equally effective as in the elderly.